Analysis of Retinal Peripapillary Segmentation in Early Alzheimer's Disease Patients. (18th October 2015) - Salobrar-Garcia, Elena; Hoyas, Irene; Leal, Mercedes; de Hoz, Rosa; Rojas, Blanca; Ramirez, Ana I.; Salazar, Juan J.; Yubero, Raquel; Gil, Pedro; Triviño, Alberto; Ramirez, José M.
Abstract : Decreased thickness of the retinal nerve fiber layer (RNFL) may reflect retinal neuronal-ganglion cell death. A decrease in the RNFL has been demonstrated in Alzheimer's disease (AD) in addition to aging by optical coherence tomography (OCT). Twenty-three mild-AD patients and 28 age-matched control subjects with mean Mini-Mental State Examination 23.3 and 28.2, respectively, with no ocular disease or systemic disorders affecting vision, were considered for study. OCT peripapillary and macular segmentation thickness were examined in the right eye of each patient. Compared to controls, eyes of patients with mild-AD patients showed no statistical difference in peripapillary RNFL thickness (P > 0.05 ); however, sectors 2, 3, 4, 8, 9, and 11 of the papilla showed thinning, while in sectors 1, 5, 6, 7, and 10 there was thickening. Total macular volume and RNFL thickness of the fovea in all four inner quadrants and in the outer temporal quadrants proved to be significantly decreased (P < 0.01 ). Despite the fact that peripapillary RNFL thickness did not statistically differ in comparison to control eyes, the increase in peripapillary thickness in our mild-AD patients could correspond to an early neurodegeneration stage and may entail the existence of an inflammatory process that could lead to progressive peripapillary fiber damage.